2004
DOI: 10.1111/j.1471-4159.2004.02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subpopulations of neurons producing melanin‐concentrating hormone in the rat ventral diencephalon

Abstract: Neurons producing melanin-concentrating hormone (MCH) are involved in a large array of functions. Some of these functions may be mediated by specific subpopulations. One such subpopulation was characterized by the expression of the neurokinin 3 receptor and the 'cocaine-and amphetamine-regulated transcript' (CART) peptide, while another expresses neither one of these two molecules. MCH+/ CART+ axons were traced throughout the brain and showed a strikingly different pattern of distribution than that of MCH+/ CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 49 publications
11
75
0
Order By: Relevance
“…Consistent with these findings, we found that OLZ induced the activation of 38% of the orexin neurons of the LH/PFA in rat brain, whereas a negligible amount of Fos-LI was seen in MCH neurons. This suggests a heterogeneity between these two groups of orexigenic neurons in regard to their neural connectivity and roles in the regulation of behavioral state (Cvetkovic et al, 2004;Modirrousta et al, 2005). Although the exact mechanism of OLZ-associated weight gain is unknown, OLZ may be better characterized by the analysis of Fos-LI in nuclei receiving projections from orexin neurons with connections to feeding-circuit regions and reward pathways of the rat brain (Harris and AstonJones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, we found that OLZ induced the activation of 38% of the orexin neurons of the LH/PFA in rat brain, whereas a negligible amount of Fos-LI was seen in MCH neurons. This suggests a heterogeneity between these two groups of orexigenic neurons in regard to their neural connectivity and roles in the regulation of behavioral state (Cvetkovic et al, 2004;Modirrousta et al, 2005). Although the exact mechanism of OLZ-associated weight gain is unknown, OLZ may be better characterized by the analysis of Fos-LI in nuclei receiving projections from orexin neurons with connections to feeding-circuit regions and reward pathways of the rat brain (Harris and AstonJones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1 A and B). Neuropeptide-glutamic acid-isoleucine (n ϭ 9), cocaine-and amphetamine-regulated transcript (n ϭ 11) and nesfatin (n ϭ 10) had no effect on MCH responsive or nonresponsive vGluT2-GnRH neurons; all three peptides can be produced by MCH neurons (51,53,54). Similarly, leptin (n ϭ 5) and NPY (n ϭ 19), which also signal availability of energy stores, had no effect on the kisspeptin-activated vGluT2-GnRH neurons.…”
Section: Mch Inhibits Vglut2-gnrh Neurons Via a Mchr1-transduced Directmentioning
confidence: 99%
“…However, much exploratory work is required to understand the regulatory network and mechanisms of action of this circuitry. Of interest to this review is the fact that the neurokinin B receptor (TACR3(NK3)) is highly expressed in a subpopulation of MCH neurones that also express the anorexigenic cocaineand-amphetamine-regulated transcript (CARTPT (CART); Griffond et al 1997, Cvetkovic et al 2004. Tachykininergic innervation of the 'MCH-containing area' (i.e.…”
Section: Part 2: Mch and Reproductive Functionmentioning
confidence: 99%